Athletes’ Sports Orientation Viewed from Parental Social Support and Gender - Olivia Rumahpasal; Wahyuni Kristinawati; Adi Setiawan (Journal Sport Area, 2020)
Sports orientation is one of the important factors for improving an athletes’ performance in achieving sports achievements. This study aims to determine the effect of parental social support and gender on athlete’s sports orientation. Quantitative approach was used as the research method of this study with a correlational research design. The subjects of study were 86 athletes (53.49 % women) at the Students Sports Training Center (SSTC) of DKI Jakarta Province who were selected through convenience sampling technique. Demographic data questionnaires, Parents Social Support Scale and Sport Orientation Questionnaires were used as the measuring instruments. Data analysis uses linear regression (simple and multiple) techniques show results as follows: (1) Parental social support has a significant effect on athletes’ sports orientation (tcount = 4.396 > ttable = 1.988); (2) Gender does not have a significant effect on athletes’ sports orientation (tcount = 1.891 < ttable = 1.988); (3) Parental social support and gender can simultaneously predict athletes’ sports orientation (Fcount = 12.93 > Ftable = 2.49). The effective contribution of parental social support and gender simultaneously toward athletes’ sports orientation is 21.9 % and the rest is influenced by other factors outside the study. The role of parental social support (17.75 %) is more dominant than gender (4.14 %)